Techniques and Materials for Treatment of Bone Loss Due to Periodontitis: A Review - S Hassani; F Hashemi moghaddam; S Akbari foroud; SH Aghayan (Islamic Azad University, 2022)
Background and Aim: Stainless steel crowns (SSCs) are the gold standard for restoration of severely damaged primary teeth. However, the unesthetic appearance of SSCs is responsible for their lower acceptance by clinicians and patients. Zirconia crowns areanother option for reconstruction of severely damaged teeth, which also provide optimal esthetics.   Case Presentation: Our patient was a 5-year-old child with acarious primary mandibular first molar. A prefabricated zirconia crown was considered for the tooth because the parents disapproved the color of SSC. The computer-aided design/computer-aidedmanufacturing (CAD/CAM) technology was used to fabricate azirconia crown with porcelain veneering since the size ofprefabricated crowns did not match the size of the respective tooth. Conclusion: At the 1-year follow-up, the crown fabricated with this technique showed optimal esthetics, function, and durability. Although these crowns have shortcomings such as the risk ofporcelain chipping, and require greater tooth preparation than SSCs, they can serve as a suitable alternative for reconstruction of severely damaged primary teeth when esthetics is an important parameter to consider.